Evaluation of Coronavirus Disease 2019-Related Anxiety, Depression, and Post-Traumatic Stress Disorder in Liver Transplantation Recipients and Their Caregivers - Adanır, Haydar; Erdoğan, Ali (Cerrahpaşa Medical Journal, 2023)
Objective: This study aimed to investigate the levels of anxiety, depression, and post-traumatic stress disorder in patients with liver transplantation and in their primary caregivers during the coronavirus disease 2019 pandemic. Methods: Forty-five liver transplant recipients and 37 primary caregivers were included in the study. The sociodemographic data form, Hospital Anxiety and Depression Scale, Beck Anxiety Inventory, and the Post-Traumatic Stress Disorder Checklist—civilian version were administered to all participants. Results: The mean age of the patients and caregivers was 51.46 ± 12.37 and 42.08 ± 15.04 years, respectively. Thirty-one percent of the patients and 70.3% of the caregivers were women. According to the Beck Anxiety Inventory, 13.3% of the patients and 21.6% of the caregivers had clinically significant anxiety, whereas 28.8% of the patients and 32.4% of the caregivers had clinically significant depression according to the Hospital Anxiety and Depression Scale scores. Post-traumatic stress disorder was determined according to Post-Traumatic Stress Disorder Checklist—civilian version in 33.3% of the patients and 48.6% of the caregivers. However, when the mean Beck Anxiety Inventory, Hospital Anxiety and Depression Scale, and Post-Traumatic Stress Disorder Checklist—civilian version scale scores of both groups were compared, no significant difference was found between the 2 groups. In the regression analysis, it was determined that each 1-point increase in Hospital Anxiety and Depression Scale depression scores resulted in a 1.314-fold significant increase in post-traumatic stress disorder scores. Conclusion: The levels of depression and post-traumatic stress disorder are significantly higher in patients with liver transplantation and their caregiv- ers during the coronavirus disease 2019 pandemic. Therefore, considering that these patients and their caregivers are not being treated for these dis- orders, the prompt identification of at-risk populations, early intervention, and effective management of diagnosed disorders are worthy of attention. Cite this article as: Adanır H, Erdoğan A. Evaluation of coronavirus disease 2019-related anxiety, depression, and post-traumatic stress disorder in liver transplantation recipients and their caregivers. Cerrahpaşa Med J. 2023;47(2):229-234.